Toy story 4 [videorecording (DVD)] (Disney, 2019)
Woody has always been confident about his place in the world and that his priority is taking care of his kid, whether that's Andy or Bonnie. But when Bonnie adds a reluctant new toy called 'Forky' to her room, a road trip adventure alongside old and new friends will show Woody how big the world can be for a toy.